Characteristics and physical mechanisms of a rainstorm in Hotan, Xinjiang, China - Yin, Gang; Zhang, Zhuo; Zhu, Bojun; Li, Qingxiang; Mao, Min; Xing, Wenyuan; Hu, Zengyun; Chen, Xi (Frontiers in Environmental Science, 2022)
Owing to global warming, extreme precipitation events in the arid regions of Central Asia have increased, resulting in significant consequences for water resources and ecosystems. Hence, to address the features and corresponding physical mechanisms of these rainstorms, we examined the rainstorm that occurred in Hotan, Xinjiang in June 2021 as a case study. We employed multiple datasets, including meteorological stations, sounding observations, satellite precipitation data, and reanalysis datasets. The results indicate that the Global Precipitation Measurement satellite precipitation product accurately captured the temporal and spatial variations in this rainstorm, as verified against hourly in-situ observation data. Some meteorological stations recorded values greater than twice their historical records, such as Luopu, Pishan, Moyu, and Hotan. Moreover, the duration of the precipitation was longer than two days. For the physical mechanisms of this rainstorm, the water vapor in this rainstorm is sourced from the 45°~65°N region of the North Atlantic Ocean crosses the Ural Mountains and the West Siberian Plain to southern Xinjiang. The low-pressure levels (e.g., 700hPa and 850hPa) have the more water vapor flux and specific humidity than the high-pressure levels. Our findings can aid the understanding of extreme precipitation events in Central Asia and provide a reference for dealing with meteorological disasters, including extreme precipitation, in the context of global climate change.